Art in dress - Philbrook, Eva (My University, 1897)
Introduction: The thought that art is something altogether outside of the common things, and affairs of life and that it is an entirely separate branch of human endeavors is erroneous. The object of art, is beauty, and this should be a quality of the simplest and most common object. Ever since the dawn of history man has been groping in a blind and helpless way for beauty. Beauty should be a quality of dress. Man is the image of God, and should make the most of himself, not only mentally and morally but also physically, and here dress may enhance beauty of form or it may destroy it, and certainly we would not want it destroyed. Beauty has been the illunderstood object of the dress maker of the past and will be the well comprehended object of the dress artist of the future. The savage, where he daubs his face with vermillion, braids his locks and adorns his braids with feathers, has the same object in view as the modern member of the “Four Hundred” when she dons her laces, ruffles, and jewels and appears in all her grandeur.
Citation: Philbrook, Eva. Art in dress. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Clothing; Art; Dressmaking; Theses; Manuscripts (documents)